INTERCULTURAL COMMUNICATION AND THE EXISTENCE OF JAMAICAN CULTURE “NAMOY BUDAYA” IN THE DIGITAL SPHERE - M. Ibnu Naufal Maskuri; Fitri Yanti; Ade Nur Istiani; Nadya Amalia Nasution; Hamdan Daulay (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
Abstract: This study aims to analyze the form of intercultural communication that occurs through the digital work